О гнездовании бекаса-отшельника (Gallinago solitaria Ноdgs.) на Алтае - Зубаровский, В.М. (Вестник зоологии, 1976)
Gallinago solitaria Hodgs make its nests in the south-western part of the Gorno-Altai Autonomous Region as micropopulations far remote one from another in the moun- tain region at a height of 2000-2500 m. Mating-call, nest biotope, nests, eggs and nestlings of young age are described. Certain phenological data are presented.